2013
DOI: 10.1021/jp408766r
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Degradation in the Reversible Hydrogen Storage Capacity of V1–xTix Alloys from the Atomic Pair Distribution Function Analysis

Abstract: Reduction in reversible hydrogen storage capacity with increasing hydrogenation and dehydrogenation cycle number is observed in numerous hydrogen storage materials, but the mechanism behind this unfavorable change has not been elucidated yet. In this study, we have investigated the development of structural defects or disorders in V1–x Ti x H2, x = 0, 0.2, and 0.5, during the first 15 hydrogen absorption and desorption cycles using the atomic pair distribution function (PDF) analysis of synchrotron X-ray total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 28 publications
(48 reference statements)
3
26
0
Order By: Relevance
“…The previous study [5] showed that dislocation migration speed to pair-annihilation is lowered by hydrogen adsorption, and remaining dislocations will cause dead storage of hydrogen to reduce the storage capacity. This mechanism supplies a good explanation for the results of Kim et al [6] on the reduction of hydrogen storage capacity and structure variation. Atomistic simulation will be useful for investigating such variation in hydrogen storage property by dislocation.…”
Section: Detailed Analyses Of Hydrogen Diffusion At Dislocation Linesupporting
confidence: 74%
See 1 more Smart Citation
“…The previous study [5] showed that dislocation migration speed to pair-annihilation is lowered by hydrogen adsorption, and remaining dislocations will cause dead storage of hydrogen to reduce the storage capacity. This mechanism supplies a good explanation for the results of Kim et al [6] on the reduction of hydrogen storage capacity and structure variation. Atomistic simulation will be useful for investigating such variation in hydrogen storage property by dislocation.…”
Section: Detailed Analyses Of Hydrogen Diffusion At Dislocation Linesupporting
confidence: 74%
“…In the previous study [5], the present author simulated point, line, and planner defects in vanadium hydride by using density functional theory and classical molecular dynamics (MD). Kim et al [6] recently observed the structure variation of vanadium hydride during hydrogen sorption cycles by X-ray total scattering. They suggested by comparing the observed and simulated values that damping of pair correlation in middle and long ranges after repeated hydrogen sorption could be explained by dislocation pileup.…”
Section: Introductionmentioning
confidence: 99%
“…Although this general awareness, the mechanism behind the degradation in the reversible hydrogen storage capacity in vanadium based alloys during hydrogen cycling was not fully elucidated. Authors of ref [39] observed an unusually rapid profile damping in the collected experimental PDFs during first hydrogen absorption and desorption cycles for pure vanadium sample with such phenomenon becoming faster by increasing the Ti concentration in the alloy. Absence of any extra peak appearing in the low r-range region during cycles ruled out the possibility of secondary phases formation as the reason for the degradation in reversible hydrogen uptake.…”
Section: Hydrogen Storage Materialsmentioning
confidence: 96%
“…For example, in Kim et al 39 the structural changes of the V 1-x Ti x alloy were investigated in the early hydrogen absorption and desorption cycles. Vanadium is a very suitable material for hydrogen storage but its high cost represents one important drawback for real applications.…”
Section: Hydrogen Storage Materialsmentioning
confidence: 99%
“…7) In our previous work, we found that there is a close correlation between reduction in the reversible hydrogen storage capacity and increase in the dislocation density in V 0.8 Ti 0.2 by hydrogen cycling. 10) Based on the findings, we suggested that cyclic stability would be improved by suppressing the formation of dislocations. In this study, we examine how the hydrogen storage properties of V 0.37 Ti 0.33 Mn 0.3 change during hydrogen cycling and investigate the effect of nitrogen, one of well known interstitial elements for solid solution hardening by dislocation pinning, 11) on the cyclic stability of V 0.37 Ti 0.33 Mn 0.3 .…”
Section: Introductionmentioning
confidence: 92%